Membangun Membangun Kebiasaan Membaca pada Anak di masa Pandemi Covid-19 melalui Program Satu Jam Tanpa Gawai di Griya Baca Desa Karangrejo - Muh. Aniar Hari Swasono; An Immatus Sa’diyah; Risdia Eka Niafitri; Rohmania Hidayanti (Jurnal Pengabdian Masyarakat, 2020)
Abstract:Starting at the endoflastyear 2019 the world was hit by a virus pandemic called Covid-19, where Indonesia also experienced the impact of this virus pandemic which caused system changes in various field sincluding in the world of education. During the Covid-19 pandemic, the learning process was carried out by providing materials and assignments through on line gadgets, starting from kinder gartent otertiary levels, which caused the intensity of deviceuse to increase. Public. The residents and youth in Dusun Karang Tengah have an advanced and creative mindset in reducing the use of gadgets during the Covid-19 pandemic. They outh and residents had the idea of ​​creating a reading house in order to reducet heuse of gadgets for children in RT 3.When there searchers came to Karangrejo Village, the making of a reading house wasstill in the process, butafter a few days, the reading house could be occupied with its seacondition. After working with community leaders there, we are also trying to realize the reading house by creating a system and providing the needs needed for this reading house. In this reading house system, we use the Assed Based Community Development (ABCD) method where we try to foster reading interest in children in reducing the use of devices during this pandemic. During the mentoring process that the researcher scarried out, there was an increase in reading interest in children in Karangtengah Hamlet, especially Rt 03 Rw 06, in the development of reading houses made as attractive as possible.